Seismic Interpretation of the Nam Con Son Basin and its Implication for the Tectonic Evolution - Tuan, Nguyen Quang; Tri, Tran Van (Indonesian Journal on Geoscience, 2016)
DOI:10.17014/ijog.3.2.127-137The Nam Con Son Basin covering an area of circa 110,000 km2 is characterized by complex tectonic settings of the basin which has not fully been understood. Multiple faults allowed favourable migration passageways for hydrocarbons to go in and out of traps. Despite a large amount of newly acquired seismic and well data there is no significant update on the tectonic evolution and history of the basin development. In this study, the vast amount of seismic and well data were integrated and reinterpreted to define the key structural events in the Nam Con Son Basin. The results show that the basin has undergone two extentional phases. The first N - S extensional phase terminated at around 30 M.a. forming E - W trending grabens which are complicated by multiple half grabens filled by Lower Oligocene sediments. These grabens were reactivated during the second NW - SE extension (Middle Miocene), that resulted from the progressive propagation of NE-SW listric fault from the middle part of the grabens to the margins, and the large scale building up of roll-over structure. Further to the SW, the faults of the second extentional phase turn to NNE-SSW and ultimately N - S in the SW edge of the basin. Most of the fault systems were inactive by Upper Miocene except for the N - S fault system which is still active until recent time.